2013
DOI: 10.14260/jemds/1647
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Meconium Aspiration and Mas (Meconium Aspiration Syndrome) in Neonates Born Through Meconium Stained Amniotic Fluid (Msaf) in a Tertiary Care Centre in Malabar (Kerala)

Abstract: U, "Risk factors for meconium aspiration and mas (meconium aspiration syndrome) in neonates born through meconium stained amniotic fluid (MSAF) in a tertiary care centre in Malabar (Kerala)".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…[15][16][17] While other studies done by Chandran et al, and Vivian -Taylor et al, proposed that post datism (>40 wks) contributed to MAS. 18,19 In present study, there were 12 ( [22][23][24] But in our study, there were no association between MAS and the route of delivery.…”
Section: Birth Asphyxiacontrasting
confidence: 57%
“…[15][16][17] While other studies done by Chandran et al, and Vivian -Taylor et al, proposed that post datism (>40 wks) contributed to MAS. 18,19 In present study, there were 12 ( [22][23][24] But in our study, there were no association between MAS and the route of delivery.…”
Section: Birth Asphyxiacontrasting
confidence: 57%
“…21,23 Mortality was 13.82% which is exactly similar to study of Jyoti et al who also reported mortality of 13.8% in MAS neonates. 24 Narang et al reported lower neonatal mortality of 7.7% whereas Gupta et al reported higher neonatal mortality of 22.2% in MAS cases. 5,6 Previous studies have shown a wide range (5-40%) in the mortality among infants with MAS, which is well correlated with this study.…”
Section: Resultsmentioning
confidence: 96%
“…5,20,21 Similar to present study, Louis et al and Jyoti et al observed higher incidence of morbidity and mortality in MAS neonates having lower APGAR score at 5 minutes of birth. 23,24 The incidence of thick meconium stained liquor was 54.3% which is significantly associated with morbidity and mortality in MAS neonates. This is in consistence with Hanoudi et al and Yong et al 16,25 In the present study, onset of respiratory distress in all the cases was since birth and 3 cases had no spontaneous respiration at birth which is similar to Louis et al according to him median age at onset of respiratory distress was 0 hour.…”
Section: Resultsmentioning
confidence: 99%
“… 11 Studies conducted in Nepal have revealed the prevalence of MSAF about 6.5%-14.6%, 8 , 9 , 12 among all live deliveries, the prevalence of MAS among MSAF about 6.6% to 8.6%, 8 , 12 and neonatal mortality from MAS about 5.4% to 11.3%. 8 , 9 , 12 The study conducted in India found the prevalence of MAS among MSAF as 7.7% to 21.5%, 4 - 6 and mortality among MAS as high as 13.8%. 4 - 6 The most common complication of MAS is Respiratory distress and other morbidities were convulsions, sepsis, shock, hypoxic-ischemic encephalopathy, hyperbilirubinemia and hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 12 The study conducted in India found the prevalence of MAS among MSAF as 7.7% to 21.5%, 4 - 6 and mortality among MAS as high as 13.8%. 4 - 6 The most common complication of MAS is Respiratory distress and other morbidities were convulsions, sepsis, shock, hypoxic-ischemic encephalopathy, hyperbilirubinemia and hypoglycemia. 13 …”
Section: Discussionmentioning
confidence: 99%